A Case of Intraductal Apocrine Carcinoma of the Breast - Kawai, Hiroshi; Imamura, Yuta; Kondoh, Aoi; Mizuno, Daisuke; Suemori, Kanto; Miyauchi, Syunsaku; Iga, Norichika; Yoshida, Ryosuke; Uno, Futoshi; Ishizaki, Masahiro; Nishi, Hideyuki; Yamashita, Kazuki; et al. (Gan to kagaku ryoho, 2021)
A female in her 60s who complained of nipple discharge in her left breast for 1 year. A soft mass ill-defined margin in the border of AB area was observed. Mammography showed a focal asymmetric density. Ultrasonography disclosed an irregular heterogenous low echoic lesion in the AB area of her left breast. MRI image showed an enhanced lesion in the inner area. The pathological diagnosis by core needle biopsy was non-invasive ductal carcinoma with apocrine metaplasia. Mastectomy with sentinel lymph node biopsy of the left breast was performed. Post operative histopathological examination revealed intraductal apocrine carcinoma without lymph node metastasis. Estrogen and progesterone receptors were negative. Three years after operation without any adjuvant treatment, she has no recurrence of lesion.